INTERPRETATION OF POTENTIALLY ACID FORMING (PAF) AND NON-ACID FORMING (NAF) DISTRIBUTION USING BLAST HOLE CUTTING SAMPLES DATA IN PIT PARINGIN AREAS PT. ADARO INDONESIA SOUTH KALIMANTAN - NORFAEDA (NIM : 22115305), RAHMA
Rock geochemical model is a geological model that describes the distribution of PAF and NAF rocks in lateral and the vertical directions on a large scale. In this research will be evaluated geochemical model on the level of blasting with actual sampling field in the form of blasthole cutting at five blasting location in highwall area Pit Paringin PT. Adaro Indonesia, and studied the mine's operating planning factors for the geochemical type of overburden. The results of blasthole cutting sample test with static geochemical test consist of pH paste, NAGpH, ABA and total sulfur used as actual model analysis data on blasting block. From the five research sites there are 3 research sites that have non-conformity with the initial geochemical model. The interpretation deviation of the PAF and NAF layer distribution model has a tendency occur in blasting blocks containing PAF and NAF layer zones. Blasting blocks that have a larger proportion of PAF layers will tend to confirm PAF-HC (high-capacity). MPA and ANC values on blasting blocks that have PAF / NAF coating concentrations have an ANC and MPA values greater than static test results of the initial geochemical model ie with MPA values participating from 57 to 104 kg H2SO4 / ton and ANC value of 18 - 48 kg H2SO4 / ton. Meanwhile, in blasting blocks that have only one PAF / NAF layer or no PAF / NAF layer coating the MPA and ANC values are equivalent to the static value range of the initial geochemical model with MPA values involved 10 - 17 kg H2SO4 / ton and ANC involvement 17 - 55 kg H2SO4 / ton.